Modeling of Uranyl Nitrate Hexahydrate Crystal Growth in Linear Crystallizer for Nano Cleaning Using SimSar Software; Key Engineering Materials; Vol. 683 : Multifunctional Materials: Development and Application - Ochoa Bique A.; Gozhimov A. I. Aleksandr Igorevich; Chursin Yu. A. Yuri Alexandrovich; Manenti F. Flavio; Schmidt O. (Elaboration and Simulation of Processes in Materials Science, 2016)
Title screen